A sustainable inventory model with controllable carbon emissions, deterioration and advance payments. (10th May 2021) - Mashud, Abu Hashan Md; Roy, Dipa; Daryanto, Yosef; Chakrabortty, Ripon Kumar; Tseng, Ming-Lang
Abstract: This study involves green technology investment to control the carbon emission from greenhouse operation and to reduce product deteriorations by applying preservation technology due to carbon emission concerns along with the preservation technology strategy is still rare in the literatures. Emissions from different industries and vehicles are the prime reason for ecological imbalance and environmental issues. Firms need to comply with ecological and social obligations to sustain operational activities. Greenhouse product retailers may utilize preservation technology to extend the product lifecycle to reduce environmental impacts. However, other logistics operations may emit CO2 into the air. This study is contributed in twofolds. (1) this study applies preservation technology how to reduce product deteriorations; and (2) this tudy proposes suitable green technology investment and preservation technology to reduce both carbon emission and product deterioration. The proposed model considers non-instantaneous deterioration, advance payments and partial backorder strategies together. The results and sensitivity analysis demonstrate the positive impacts of controllable carbon emission and deterioration on the total inventory model profit. The cases illustrate 12% increased in the total profit from green technology investment and 23% increased from both preservation and green technology investments. Graphical abstract: Image 1 Highlights: This study concerns on greenhouse product retailers that invest in preservation and green technology. The investments reduce the product deterioration rate and carbon emissions. This study aims at maximizing total profit while controlling the environmental impact. The model simultaneously considers non-instantaneous deterioration, advance payments and partial backorder.